The effect of infrared radiation emitting garments on oxygen uptake kinetics and oxygen cost during moderate intensity cycling - Bond, J.; Bailey, S.; Brownstone, T.; Ferguson, R. (Journal of Science and Cycling, 2024)
Introduction Oxygen uptake (VO2) kinetics are an important determinant of exercise performance (Burnley & Jones, 2007). Speeding VO2 kinetics can spare anaerobic energy stores at the onset of exercise, consequently enhancing exercise performance (Bailey et al, 2009). Both exercise training (Jones et al, 2011) and dietary interventions (e.g. nitrate supplementation; Vanhatalo et al, 2010) have been shown to alter VO2 kinetics. KYMIRA garments, powered by Celliant, are a novel infrared (IR) emitting fabric that re-emit absorbed body heat as IR. IR emission has been shown to increase blood flow during exercise (Katsuura et al, 1989) which could increase muscle oxygen delivery, and potentially alter VO2 kinetics. Indeed, previous work has shown that IR emission using similar garments reduced the oxygen cost of cycling (Worobets, Skolnik, & Stefanyshyn, 2015), although VO2 kinetics have not been systematically investigated. The aim of this study was to investigate whether KYMIRA garments alter VO2 kinetics and oxygen cost during moderate intensity cycling.